(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article reflects on the emergency conditions of the Application Schools (CAPs) in Brazil, based on a brief historical overview of the creation of these educational institutions and their role in the training of students and teachers. The text links the creation of CAPs to significant transformations envisaged in the first decades of the 20th century. CAPs are idealized as a field of teaching practice and research for students of Didactics courses, which gives them a differentiated and, to a certain extent, elitist nature. The text ends with a reflection on the reality of the CAP of the Federal University of Rio Grande do Sul (UFRGS), with regard to the teaching of Theater, showing favorable conditions for pedagogical work and the learning of knowledge related to this artistic area.